Quality assessment and storage study of choco milk produced by the Negros Federation of Dairy Cooperative - Gallego, Jessa Jhoy Anas (2007.)
The choco milk processed in different batches and stored at room, chilling, and freezing temperatures was assessed for quality consistency.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Choco milk; Negros Federation of Dairy Cooperative